Employee Performance: Effect of Competency and Quality of Work-life - Poppy Arnold Kadir; M. Liga Suryadana (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
This study aims to determine competence, quality of work-life and employee performance in one of the hotels in the city of Bandung and to analyze the influence of competence on employee performance and the influence of the quality of work-life on employee performance and the influence of competence and quality of work-life together on employee performance. The method used in this research is a survey method with an associative explanation level. Respondents in this study were 95 employees. The data collection techniques used literature study, documentation study, and field study using interviews and questionnaires. The data analysis technique used is a quantitative analysis and statistical analysis. The quantitative analysis includes the respondent's score, while the statistical analysis uses path analysis. The finding shows there is a positive relationship between competence and performance of 0.418, there is a positive relationship between the quality of work-life and performance of 0.596. there is a positive relationship between competence and quality of work-life of 0.371 and epsilon (factors others not researched) of 0.286.